Twenty-six years of aspen regeneration under varying light conditions in a boreal mixedwood forest - Holly D. Deighton; Arthur Groot; Nelson Thiffault; Mya Rice (The Forestry Chronicle)
Density, height, and diameter at breast height of trembling aspen (Populus tremuloides Michx.) sucker regeneration were assessed over a 26-year period in openings created by harvesting in a 40-year-old aspen stand in northeastern Ontario (Canada). The opening types were 9- and 18-m diameter circles, 9- and 18- _ 150-m east-west strips, and a 100- _ 150-m clearcut, representing a range of light conditions. Density, height, and diameter at breast height of aspen regeneration were significantly affected by opening type, location relative to opening, and time since harvest. By year 26, aspen densities in circular openings declined to 0, despite high initial recruitment, and trembling aspen heights were significantly lower in the 9-m strips than in the 18-m strips or the clearcut. Year 26 aspen density, volume, and basal area increased with increasing initial light intensity, with the highest rate of increase between 80 and 100% light levels. Understory vegetation cover was largely unaffected by opening size; however, substantial understory aspen regeneration occurred in the smaller openings. Results support the traditional view that aspen is best managed under the clearcut silvicultural system, and >80% full light is recommended for adequate long-term aspen regeneration.